2020
DOI: 10.1167/tvst.9.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Light Sword Lens for Presbyopia Correction

Abstract: We propose and evaluate the modifications of a light sword lens (LSL) to obtain better performance for distance vision while maintaining good operation for near and intermediate vision. Methods: The modifications consisted of assigning angular or circular windows for distance vision while rescaling the LSL profile in the remaining area of the element. The objective performance of the redesigned LSLs was verified numerically by the Strehl ratio and experimentally using correlation coefficients and Michelson con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“… 71 Another EDOF technique, light sword lenses, is an asymmetric refractive element with angular variation of optical power. 72 Experimental results showed that light sword lenses produced consistently good quality images at a wide range of distances from 25 to 33 ​cm to infinity, and a recent clinical study showed their acceptable VA and high-quality contrast sensitivity at near and distant vision. 73 Overall, all these new EDOF designs represent promising alternatives for presbyopia correction in clinical applications.…”
Section: Intraocular Lens (Iol) For Presbyopia Correctionmentioning
confidence: 88%
“… 71 Another EDOF technique, light sword lenses, is an asymmetric refractive element with angular variation of optical power. 72 Experimental results showed that light sword lenses produced consistently good quality images at a wide range of distances from 25 to 33 ​cm to infinity, and a recent clinical study showed their acceptable VA and high-quality contrast sensitivity at near and distant vision. 73 Overall, all these new EDOF designs represent promising alternatives for presbyopia correction in clinical applications.…”
Section: Intraocular Lens (Iol) For Presbyopia Correctionmentioning
confidence: 88%
“…Other designs being explored have unique angular optical elements [97]. One such lens is called the "light sword lens" [98][99][100][101], which is an asymmetric optical element divided into infinitesimal angular sectors, each with different additions of optical power [98]. Another unique design theorised is called the "peacock optical element", which is a particular type of diffractive element capable of focusing light onto segments of arbitrary length, inclination, orientation, and longitudinal intensity distribution [102,103].…”
Section: Extended Depth Of Focus (Edof)mentioning
confidence: 99%
“…Two important ones are the semicircle split bifocal, which includes two commercial models [7], and the triangulate trifocal. To my knowledge, the only pseudo-continuous profile involving both radial and angular profiles is the so-called light sword element [8][9][10][11][12][13][14]. Yet, the light sword lens contains an abrupt discontinuity along a line, although some variants have also been proposed to avoid that discontinuity [11].…”
Section: Introductionmentioning
confidence: 99%